Construction of Ibn 'Aṭāillāh al-Sakandarī's Tafsir: Tracing Sufistic Epistemology in Qur’anic Interpretation - Kharomen, Agus Imam; In’amuzzahidin, Muh.; Meilia, Dika; Anwar, Noer Faizah (Teosofia: Indonesian Journal of Islamic Mysticism, 2023)
This study aims to reveal the interpretation of Ibn 'Aṭāillāh, spread in his Sufism books. Apart from a historical approach, this library research applies a hermeneutic approach to understand the form of Ibn 'Aṭāillāh's Sufistic interpretation. The results reveal that Ibn ‘Aṭāillāh's tafsir product includes 630 verses from 89 surahs. The tafsir epistemology applied by Ibn 'Aṭāillāh uses a Sufism approach to reveal the wisdom of the Qur'an. His motivation is to provide guidance for the salik or spiritual travellers and position the Quran as a source of wisdom and the basis for the concept of Sufism. Ibn 'Aṭāillāh Sufistic interpretation complements other tafsir products and emphasises that the style of interpretation is determined by the approach used by the mufassir and the importance of positioning the Qur'an as a source for understanding religion.Contribution: This research contributes to revealing the Sufistic style of interpretation, which is not limited to verses dealing with ethics. The interpretation style lies in the approach rather than in the theme discussed. All verses can be approached from a Sufistic perspective, as conducted by Ibn 'Aṭāillāh.